Methodology for controlling the ship's path during the turn in confined waterways - Vujičić, Srđan, inženjer pomorske tehnologije (Array, 2018)
One of the basic tasks in the shipping industry is to ensure safe manoeuvring and navigation through channels and confined waterways. This paper has presented a practical and theoretical approach to the assessment of safe manoeuvring in waterways based on knowledge and experience. Experienced mariners had to sail through an approach to Thorn channel in a calm weather using their own knowledge and methods to determine variable angles of rudder deflection. The navigational performance has been determined in terms of deviation from the intended path. The results have indicated the difference in distances of the ship paths between all respondents as compared to the intended path. Besides determining the ship’s turn path, it is necessary to consider the factor F which represents the distance between the WOP and the beginning of the actual turn and the width of the swept track. However, the aim of this paper is to present a control methodology for mariners while working at sea.